Influence of P-wave oblique incidence on seismic response of helical piles in soft soil sites - Hang Cen; Hui-yue Wang; De-long Huang; Jian-rong Xu; Sha-sha Yu; Chang-lu Xu; Zhong-ling Zong; Wen Zhou; Zi-yuan Huang (Scientific Reports)
Abstract In regions susceptible to earthquakes, an increasing number of building structures are employing helical piles as their foundational system due to their commendable seismic performance. This paper investigates the vertical displacements of the helical pile-soil model, dynamic p-y curves, and seismic subsidence of helical piles in marine soft soil sites under seismic motions, considering the effects of various types of seismic waves, seismic intensity, angle of incidence, and the number of helical blades. The results demonstrate that the vertical displacement of double-blade helical piles is smaller than that of single-blade helical piles. Furthermore, the vertical displacement of helical pile-soil systems is influenced by the type of seismic wave, seismic intensity, and angle of incident. Moreover, the seismic subsidence of helical piles is significantly influenced by the peak ground acceleration and the frequency of the seismic wave, both of which are related to the angle of incident. Finally, this paper rectifies the p-y curve of soft soil in the API specification based on the angle of incidence. The conclusions of this study provide a basis for the seismic design of helical piles in marine soft soil sites.